Refugees, Refuge, and Human Displacement - López-Calvo, Ignacio (Anthem studies in Latin American literature and culture., 2022)
This volume studies the concept of refuge as well as historical forced displacement and statelessness, trying to provide potential lasting solutions to the many problems associated with this situation. It moves from the pressing crisis of refugees to the crisis of humanity that seeks to find refuge.